2022
DOI: 10.3390/nu14153108
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Derived Beneficial for Blood Pressure Dietary Pattern Associated with Hypertension Prevention and Control: Based on China Nutrition and Health Surveillance 2015–2017

Abstract: Background: Greater adherence of Dietary Approach to Stop Hypertension (DASH) or the Mediterranean dietary pattern were reported to be beneficial for blood pressure. However, both were established based on Western populations. Our current study aimed to explore a dietary pattern which might be suitable for hypertension prevention and control among Chinese adults nationwide. Methods: A total of 61,747 Chinese adults aged over 18 years from China Nutrition and Health Surveillance 2015–2017 was included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…After title and abstract screening, 136 articles were assessed for eligibility. The final sample of the study incorporated 12 individual studies [ 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Figure 1 presents the details of the study search and selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After title and abstract screening, 136 articles were assessed for eligibility. The final sample of the study incorporated 12 individual studies [ 14 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Figure 1 presents the details of the study search and selection process.…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot for the hypertension risk when cross-sectional studies were pooled together. Cherfan et al, 2019 (M) [ 30 ], Cherfan et al, 2019 (W) [ 30 ], Kanauchi & Kanauchi, 2015 [ 15 ], Yang et al, 2022 [ 31 ]. …”
Section: Figurementioning
confidence: 99%
“…A cross-sectional study, China Nutrition and Health Surveillance among Chine’s adult reported posterior dietary pattern extracted with selected micronutrients as response variables in RRR method and priori DASH diet-score calculated to validate the dietary pattern derived by RRR method 78 . The posterior DP was characterized by higher fresh vegetables, fruits, dairy products, less refined grains and alcohol consumption and healthy food items in Chines dietary culture, along with DASH diet presented the protective effects on both hypertension prevention and control 78 .…”
Section: Discussionmentioning
confidence: 99%
“…The average value of the three-times systolic blood pressure (SBP) and diastolic blood pressure (DBP) was used for the data analysis. Hypertension was defined as SBP ≥ 140 mmHg and (or) DBP ≥ 90 mmHg and (or) receiving antihypertensive medications within two weeks [22].…”
Section: Anthropometric Measurement and Definition Of Hypertensionmentioning
confidence: 99%